Village Fund Governance in Realizing Justice and Public Welfare Based on Siyasah Sharʿiyyah location (The case study in Pekon Way Batang, Indonesia) - Umaro, Ilham; Karini, Eti; Burhanuddin, Ahmad (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
This study examines the management of Village Funds in Pekon Way Batang, Lemong District, Pesisir Barat Regency, through the normative-empirical framework of siyāsah shar‘iyyah. The urgency of this research lies in the limited scholarly integration between positive law perspectives and Islamic ethical-moral principles in Village Fund governance. This field research employs a qualitative juridical-empirical approach. Primary data were collected through interviews with village officials, community leaders, youth representatives, and local residents, while secondary data were derived from statutory regulations and relevant documents. The findings indicate that Village Fund management is relatively participatory, transparent, and responsive to community needs, particularly through Village Deliberation (Musyawarah Desa) mechanisms. From the perspective of siyāsah shar‘iyyah, these practices reflect the implementation of justice (al-‘adl), consultation (shūrā), and public welfare orientation (al-maṣlaḥah al-‘āmmah). Budget prioritization for vulnerable groups demonstrates distributive justice, while budget transparency and complaint mechanisms embody the contemporary function of hisbah (public oversight). Nevertheless, limited human resource capacity among village officials remains a structural challenge that may affect administrative effectiveness and sustainability. Overall, Village Fund governance in the research location tends to align with the principles of siyāsah shar‘iyyah, although institutional strengthening and enhanced supervisory mechanisms are necessary to achieve substantive justice and optimal public welfare.